Juridical Analysis of Regional Government Policies in The Protection and Empowerment of Farmers in Bima Regency - Vemansyah, Bimo; Firmanto, Taufik; Gufran, Gufran (Jurnal Mediasas: Media Ilmu Syari'ah dan Ahwal Al-Syakhsiyyah, 2025)
This study aims to analyze the regional government's policy in Bima Regency regarding the legal protection and empowerment of farmers. Referring to Law Number 19 of 2013 concerning the Protection and Empowerment of Farmers, local governments are mandated to ensure farmers' welfare through legal protection, access to agricultural inputs, and capacity strengthening. This study adopts a mixed methods approach, integrating both normative (doctrinal) and empirical (non-doctrinal) legal research. The normative dimension examines statutory frameworks, while the empirical component captures socio-legal realities through field data. The findings indicate that although a regional regulation exists to support these efforts, its implementation faces numerous challenges such as limited budget, weak dissemination, inadequate infrastructure, and low farmer participation in policy-making and evaluation. The juridical analysis reveals a significant gap between legal norms and social realities, resulting in suboptimal policy execution. This study recommends a more participatory policy reformulation, strengthening of farmer institutions, and the utilization of digital technology to support sustainable agricultural development. [Penelitian ini bertujuan untuk menganalisis kebijakan pemerintah daerah di Kabupaten Bima terkait perlindungan hukum dan pemberdayaan petani. Merujuk pada Undang-Undang Nomor 19 Tahun 2013 tentang Perlindungan dan Pemberdayaan Petani, pemerintah daerah memiliki kewajiban untuk menjamin kesejahteraan petani melalui perlindungan hukum, akses terhadap sarana produksi pertanian, dan penguatan kapasitas. Penelitian ini menggunakan pendekatan campuran (mixed methods), yang menggabungkan penelitian hukum normatif (doktrinal) dan empiris (non-doktrinal). Pendekatan normatif digunakan untuk mengkaji kerangka regulasi, sedangkan pendekatan empiris bertujuan untuk menangkap realitas sosial-hukum melalui data lapangan. Temuan penelitian menunjukkan bahwa meskipun terdapat peraturan daerah yang mendukung upaya tersebut, pelaksanaannya masih menghadapi berbagai tantangan seperti keterbatasan anggaran, lemahnya sosialisasi, infrastruktur yang belum memadai, serta rendahnya partisipasi petani dalam proses perumusan dan evaluasi kebijakan. Analisis yuridis mengungkapkan adanya kesenjangan signifikan antara norma hukum dan realitas sosial, yang berdampak pada kurang optimalnya pelaksanaan kebijakan. Penelitian ini merekomendasikan reformulasi kebijakan yang lebih partisipatif, penguatan kelembagaan petani, serta pemanfaatan teknologi digital untuk mendukung pembangunan pertanian yang berkelanjutan.]